Sulfated glycoconjugates enhance CD36-dependent adhesion of Plasmodium falciparum-infected erythrocytes to human microvascular endothelial cells. - McCormick, C; Newbold, C; Berendt, A (2000)
A novel adhesive pathway that enhances the adhesion of Plasmodium falciparum-infected erythrocytes (IEs) to endothelial cells has been identified. The sulfated glycoconjugates heparin, fucoidan, dextran sulfate 5000, and dextran sulfate 500 000 caused a dramatic increase in adhesion of IEs to human dermal microvascular endothelial cells. The same sulfated glycoconjugates had little effect on IE adhesion to human umbilical vein endothelial cells, a CD36-negative cell line. The effect was abolished by a monoclonal antibody directed against CD36, suggesting that enhanced adhesion to endothelium is dependent on CD36. No effect was observed on adhesion to purified platelet CD36 cells immobilized on plastic. The same sulfated glycoconjugates enhanced adhesion of infected erythrocytes to COS cells transfected with CD36, and this was inhibited by the CD36 monoclonal antibody. These findings demonstrate a role for sulfated glycoconjugates in endothelial adherence that may be important in determining the location and magnitude of sequestration through endogenous carbohydrates. In addition, they highlight possible difficulties that may be encountered from the proposed use of sulfated glycoconjugates as antiadhesive agents in patients with severe malaria.